Correction: A thesaurus for improved communication and data integration in sandy beach ecosystem research - Senem Onen Tarantini; Jessica Titocci; Andrea Tarallo; Omar Defeo; Thomas Schlacher; Guilherme Corte; Carlos Alberto de Moura Barboza; Leonardo Lopes Costa; Ivan Franco Rodil; Linda R. Harris; Jeffrey A. Sibaja-Cordero; Martina Pulieri; et al. (Earth Science Informatics, 2026)

A thesaurus for improved communication and data integration in sandy beach ecosystem research - Senem Onen Tarantini; Jessica Titocci; Andrea Tarallo; Omar Defeo; Thomas Schlacher; Guilherme Corte; Carlos Alberto de Moura Barboza; Leonardo Lopes Costa; Ivan Franco Rodil; Linda R. Harris; Jeffrey A. Sibaja-Cordero; Martina Pulieri; et al. (Earth Science Informatics, 2026)

Assessing the impact of a major electronic music festival on the consumption patterns of illicit and licit psychoactive substances in a Mediterranean city using wastewater analysis - Ivan Senta; Ivona Krizman-Matasic; Petra Kostanjevecki; Iria Gonzalez-Mariño; Rosario Rodil; José Benito Quintana; Iva Mikac; Senka Terzic; Marijan Ahel (Science of The Total Environment, 2023)

Ocean acidification and warming gradients modulate interaction strength between different mesograzers and macroalgae - Sampaio Eduardo; Rodil Ivan; Vaz-Pinto Fatima; Fernandez Angela; Arenas Francisco (Frontiers in Marine Science, 2016)

The targeting of large-sized benthic macrofauna by an invasive portunid predator: evidence from a caging study - Michael Townsend; Andrew M. Lohrer; Ivan F. Rodil; Luca D. Chiaroni (Biological Invasions, 2015)

Experimenting with ecosystem interaction networks in search of threshold potentials in real‐world marine ecosystems - Simon F. Thrush; Judi E. Hewitt; Samantha Parkes; Andrew M. Lohrer; Conrad Pilditch; Sarah A. Woodin; David S. Wethey; Mariachiara Chiantore; Valentina Asnaghi; Silvia De Juan; Casper Kraan; Ivan Rodil; et al. (Ecology, 2014)
Thresholds profoundly affect our understanding and management of ecosystem dynamics, but we have yet to develop practical techniques to assess the risk that thresholds will be crossed. Combining ecological knowledge of critical system interdependencies with a large‐scale experiment, we tested for breaks in the ecosystem interaction network to identify threshold potential in real‐world ecosystem dynamics. Our experiment with the bivalves Macomona liliana and Austrovenus stutchburyi on marine sandflats in New Zealand demonstrated that reductions in incident sunlight changed the interaction network between sediment biogeochemical fluxes, productivity, and macrofauna. By demonstrating loss of positive feedbacks and changes in the architecture of the network, we provide mechanistic evidence that stressors lead to break points in dynamics, which theory predicts predispose a system to a critical transition.

Processing of allochthonous macrophyte subsidies by sandy beach consumers: estimates of feeding rates and impacts on food resources - Mariano Lastra; Henry M. Page; Jenifer E. Dugan; David M. Hubbard; Ivan F. Rodil (Marine Biology, 2008)